In utero ethanol exposure induces mitochondrial DNA damage and inhibits mtDNA repair in developing brain - Darbinian, Nune; Darbinyan, Armine; Merabova, Nana; Kassem, Myrna; Tatevosian, Gabriel; Amini, Shohreh; Goetzl, Laura; Selzer, Michael E. (Frontiers in Neuroscience, 2023)
Introduction Mitochondrial dysfunction is postulated to be a central event in fetal alcohol spectrum disorders (FASD). People with the most severe form of FASD, fetal alcohol syndrome (FAS) are estimated to live only 34 years (95% confidence interval, 31 to 37 years), and adults who were born with any form of FASD often develop early aging. Mitochondrial dysfunction and mitochondrial DNA (mtDNA) damage, hallmarks of aging, are postulated central events in FASD. Ethanol (EtOH) can cause mtDNA damage, consequent increased oxidative stress, and changes in the mtDNA repair protein 8-oxoguanine DNA glycosylase-1 (OGG1). Studies of molecular mechanisms are limited by the absence of suitable human models and non-invasive tools. Methods We compared human and rat EtOH-exposed fetal brain tissues and neuronal cultures, and fetal brain-derived exosomes (FB-Es) from maternal blood. Rat FASD was induced by administering a 6.7% alcohol liquid diet to pregnant dams. Human fetal (11–21 weeks) brain tissue was collected and characterized by maternal self-reported EtOH use. mtDNA was amplified by qPCR. OGG1 and Insulin-like growth factor 1 (IGF-1) mRNAs were assayed by qRT-PCR. Exosomal OGG1 was measured by ddPCR. Results Maternal EtOH exposure increased mtDNA damage in fetal brain tissue and FB-Es. The damaged mtDNA in FB-Es correlated highly with small eye diameter, an anatomical hallmark of FASD. OGG1-mediated mtDNA repair was inhibited in EtOH-exposed fetal brain tissues. IGF-1 rescued neurons from EtOH-mediated mtDNA damage and OGG1 inhibition. Conclusion The correlation between mtDNA damage and small eye size suggests that the amount of damaged mtDNA in FB-E may serve as a marker to predict which at risk fetuses will be born with FASD. Moreover, IGF-1 might reduce EtOH-caused mtDNA damage and neuronal apoptosis.